Binge Drinking: In Search of its Molecular Target via the GABAA Receptor - Yang, Andrew R.; Liu, Juan; Yi, Heon S.; Warnock, Kaitlin T.; Wang, Mingfei; June, Jr., Harry L.; Puche, Adam C.; Elnabawi, Ahmed; Sieghart, Werner; Aurelian, Laure; June, Sr., Harry L. (Frontiers in Neuroscience, 2011)
Binge drinking, frequently referred to clinically as problem or hazardous drinking, is a pattern of excessive alcohol intake characterized by blood alcohol levels [BALs] > 0.08 g% within a 2 h period. Here, we show that overexpression of α1 subunits of the GABAA receptor contributes to binge drinking, and further document that this involvement is related to the neuroanatomical localization of 1 receptor subunits. Using a herpes simplex virus amplicon vector to deliver small interference RNA [siRNA], we showed that siRNA specific for the a1 subunit [pHSVsiLA1] caused profound, long-term, and selective reduction of gene expression, receptor density, and binge drinking in high alcohol drinking [HAD] rats when delivered into the ventral pallidum [VP]. Scrambled siRNA [pHSVsiNC] delivered similarly into the VP failed to alter gene expression, receptor density, or binge drinking. Silencing of the 1 gene in the VP, however, failed to alter binge sucrose or water intake. These results, along with our prior research, provide compelling evidence that the a1-containing GABAA receptor subunits are critical in the regulation of binge-like patterns of excessive drinking. Collectively, these data may be useful in the development of gene-based and novel pharmacological approaches for the treatment of excessive drinking.